Portrayal of fisher's life in tamil cinema - Koduthor, S.J.D. (University of Jaffna, 2020)
The twenty first century is an information age. Media becomes an ever more powerful force in shaping the world's perception of itself, an individual's struggle to maintain a unique identity and self-understanding. Tamil cinema also has such a rapid growth recently and becomes popular in India. The main objective of this research is to analyze about how Tamil cinema portrayed or represents in the sense of expressing fisher’s life & their life style in a general manner. Plot will be more attractive through the theme and setting of the cinema. For theoretical frame work this study has the auteur theory for its theoretical framework. Identifying how Tamil films portraying fisher’s life and representing their life with their difficulties and challenges fully? This is the main research question for this research. The hypothesis of this study is, the films which were directed by south Indian film directors, they talk about much more variety of themes even including about the fisher’s life. But in some time, they failed to portray some matters of fisher’s life and coastal area issues in an appropriate way. The scope of this study is that, nine films which were released after the year of 2000. This research has done with the quantitative and qualitative method including interview to collect data and with those data the researcher has done comparative and content analysis to find out the results for these research questions. According to that, the researcher has focused some factors throughout this research and found that Tamil films utilize different method to bring out Fisher’s life with the poverty line, love & marriage, Religion, structure of caste, level of education, travelling, language, and family life. According to the data collection, the primary data were collected as selected films through DVDs. And the secondary data were collected as through the books, journals, articles and interviews
Keywords: plot; structure; tamil cinema; theme